2003
DOI: 10.1177/03635465030310012001
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Glenohumeral Osteoarthrosis in Unstable Shoulders

Abstract: The overall prevalence of glenohumeral osteoarthrosis was low. Predictors of osteoarthritis included time from injury to surgery and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 7 publications
2
79
0
4
Order By: Relevance
“…The average  SD age of all patients in this group was 32.6  11.9 years, which is similar to that found in other studies. 7,8,33 The average  SD age of patients having a rotator cuff repair in this study was similar to findings of other investigators, 14,25,34,36 but younger than that reported by Boissonnault et al 3 (67.0  8.6 years) and others. 20,37 It is not clear why patients in this study were younger.…”
Section: Patient Outcomes Related To Disabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…The average  SD age of all patients in this group was 32.6  11.9 years, which is similar to that found in other studies. 7,8,33 The average  SD age of patients having a rotator cuff repair in this study was similar to findings of other investigators, 14,25,34,36 but younger than that reported by Boissonnault et al 3 (67.0  8.6 years) and others. 20,37 It is not clear why patients in this study were younger.…”
Section: Patient Outcomes Related To Disabilitysupporting
confidence: 91%
“…This descriptive report of clinical and utilization outcomes may assist clinicians in understanding the typical patient response to postoperative physical therapy management. pression for impingement syndromes, 19 repair of instability conditions, 7,8,24 and fractures. Although most shoulder pain is related to disorders of the rotator cuff, such as impingement or cuff tears, uncertainty exists regarding the effectiveness of medical and surgical interventions.…”
mentioning
confidence: 99%
“…''Dislocation arthropathy'' occurs in patients treated nonoperatively and operatively. Intraarticular changes may occur following a single dislocation, and can worsen with subsequent instability episodes [8,10,15,18,24].…”
Section: Discussionmentioning
confidence: 99%
“…Early degenerative joint disease can mimic or coexist with other pathologic diagnoses, such as impingement [2,6,8]. For early stage arthritis, particularly small focal lesions not easily elucidated by plain radiographs or MR imaging, arthroscopy can be an important diagnostic tool [2].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4]7,10 This management has not gained universal acceptance due to controversy over possible increased rates of arthritic changes in the surgically stabilized shoulder in addition to the recognized risks of surgery. 1,9,37 Anterior shoulder dislocations are frequently accompanied by avulsions of the labrum from the glenoid. 13,17,20,27,35 Both in vivo and cadaver studies have determined that the typical sling immobilization position of internal rotation and adduction maintains the avulsed labrum away from the glenoid.…”
mentioning
confidence: 99%